ChemInform Abstract: β‐Cyclodextrin—TiO2: Green Nest for Reduction of Nitroaromatic Compounds. Issue 16 (April 2015) - Kakroudi, Mazaher Abdollahi; Kazemi, Foad; Kaboudin, Babak
Abstract The TiO2/β‐CD guest‐host catalytic system (called ′green nest′) can be recycled and reused at least 3 times with moderate decrease in yield maybe due to partial loss of photocatalyst.